2009
DOI: 10.1111/j.1365-2672.2008.04061.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of salicylates against hydrogen peroxide stress in yeast

Abstract: Aims:  To investigate the effects of salicylates in Saccharomyces cerevisiae exposed to oxidative stress induced by hydrogen peroxide (H2O2). Methods and Results:  Saccharomyces cerevisiae was cultured through to the postlogarithmic phase of growth. Stress was induced by the addition of 1·5 mmol l−1 H2O2 for 1 h, while N‐acetyl‐l‐cysteine (NAC) and glutathione (GSSG) were used as control agents that affect the redox balance. Sodium salicylate, at 0·01–10 mmol l−1or acetylsalicylic acid, at 0·02–2·5 mmol l−1 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…This is consonant with the concept that oxidative stress, however produced, regulates the level of apoptosis in yeast (Madeo et al, 1999). On the other hand, there is also evidence in support of aspirin acting as a cytoprotective antioxidant by scavenging of ROS (Yiannakopoulou & Tiligada, 2009;Baltazar et al, 2011). This dichotomous nature of aspirin as both pro-oxidant and antioxidant is reflected in various conflicting reports on effects of aspirin on the superoxide dismutases (SODs) and other antioxidant enzymes.…”
Section: Introductionmentioning
confidence: 58%
“…This is consonant with the concept that oxidative stress, however produced, regulates the level of apoptosis in yeast (Madeo et al, 1999). On the other hand, there is also evidence in support of aspirin acting as a cytoprotective antioxidant by scavenging of ROS (Yiannakopoulou & Tiligada, 2009;Baltazar et al, 2011). This dichotomous nature of aspirin as both pro-oxidant and antioxidant is reflected in various conflicting reports on effects of aspirin on the superoxide dismutases (SODs) and other antioxidant enzymes.…”
Section: Introductionmentioning
confidence: 58%
“…Salicylate has antioxidant properties and has been used to protect cells from oxidative stress (Althaus et al, 1993; Kojda, 2004; Speir et al, 1998; Yiannakopoulou et al, 2009). Several studies have found that salicylate protects against ototoxicity and noise-induced hearing loss (Chen et al, 2007; Kopke et al, 2000; Li et al, 2002; Sha et al, 1999; Sha et al, 2006; Yamashita et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, the cellular prooxidant behavior of NSAIDs has often been the subject of controversy owing to conflicting reports that NSAIDs such as indomethacin and sulindac scavenge ROS and exert a cytoprotective and antioxidant effect in cells [68,69]. It has also been shown that low doses of aspirin can confer long-term cytoprotective resistance against H 2 O 2 -induced oxidative stress in Saccharomyces cerevisiae cells [70]. Nevertheless, it has been accepted that NSAIDs can induce the proapoptotic accumulation of ROS in mammalian cells.…”
Section: Enhancing Host Defense Phase 2 Enzyme Responsementioning
confidence: 99%